Aplikasi Sistem Antar Jemput Berbasis Mobile - Yudi Hadi Saputra; Lily Puspa Dewi; Anita Nathania Purbowo (Jurnal Infra, 2019)
School and university transfers are widely used, but the location of the shuttle at this time cannot be tracked. Viewed from this aspect the user needs a system that can see the location of the shuttle vehicle and a system that is able to connect between the owner, driver and user. Viewed from the aspect of the driver, the driver also needs a system that is able to provide navigation guidance on routes that can be used to get to a place or destination.This Android-based shuttle system application is intended to help owners, drivers and users to improve the quality of the shuttle system. This application will be made using the Java language using Android Studio. This mobile based application helps the owner to determine the schedule every week and every day, monitor the location of each driver. In addition, it can help the driver to get navigation about the route to reach a location or destination.The test results show that this application runs well on devices such as Android 6.0.1 (Marshmallow). This application runs weekly and daily schedule settings, notification features, displays driver information, chat features, and navigation features making it easier for drivers to use the best routes.